Quand les jardins résistent à l’art… - Catherine Chomarat-Ruiz (Projets de Paysage)
This paper inquires about what is not concerning art in the gardens. It considers the idea that if gardens are accustomed to borrow from the other arts – painting, theater, etc. – there is not a specific garden art. Then it develops two hypothesis: in the heart of garden, wouldn’t it nature, or sciences and techniques that avoid the influence of art? According to the limits of these two possibilities, it establishes that it is outside the garden that something escapes the power of art: it seems that it’s the landscape. It deduces a definition of garden founded in gardening which, different from landscape planning, would be a specific garden art.